ANTI-OBESITY POTENTIALS OF AQUEOUS AND METHANOL EXTRACTS OF Vernonia amygdalina DEL. LEAVES IN HIGH-FAT DIET FED RATS - Egedigwe, Chima Agatha; Ejike, Chukwunonso E.C.C.; Ijeh, Ifeoma I.; Herbert, Udo; Onwuka, Gregory I.; Asumugha, Victoria U. (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Obesity is currently a global epidemic. Conventional treatments have not been very satisfactory to patients, warrantinga search for alternative therapeutic options that are natural, safe and affordable. This study therefore investigated the anti-obesitypotentials of aqueous and methanol extracts of Vernonia amygdalina Del (AEVA and MEVA respectively) in a rat model in whichobesity was induced using a high-fat diet.Materials and Methods: Forty two Wistar rats were randomised into 7 groups of 6 rats each. One group served as the NormalControl group and obesity was induced in the other 6 groups. One of the 6 groups each served as Positive Control and NegativeControl while the 4 test groups were designated AEVA100, AEVA500, MEVA50 and MEVA200, respectively. The study lasted for12 weeks after which standard protocols were followed for all analyses and determinations.Results: The results show that both AEVA and MEVA at the tested concentrations resulted in significant (P < 0.05) weight loss(without affecting internal organs negatively), and significant (P < 0.05) improvement in some metabolic markers of obesity in thetest rats compared to the negative control rats. MEVA 200 had the greatest anti-obesity effect while MEVA 50 was the leasteffective. All the test extracts compared well with Orlistat used as the positive control drug on all counts.Conclusion: The observed weight-loss benefits of AEVA and MEVA are attributable to the rich milieu of phytochemicals found inVernonia amygdalina Del. Further studies to unlock the mechanisms through which the observed weight loss is mediated arewarranted.